POLA BAGI HASIL PADA PERIKANAN TANGKAP DI KELURAHAN TANJUNG LAUT INDAH KOTA BONTANG - Reza Nazwan; Qoriah Saleha; Oon Darmansyah (2339-1324, 2019)
This research aims to analyze the business and the profit sharing pattern of fisheries fishermen in Tanjung Laut Indah Village. The research used the survey method and applied purposive sampling that selected 45 respondents based on 3 types of fishing gear. The respondents composed by 15 owners and 30 crews of capture fisheries business. The method of data analysis using qualitative and quantitative analysis. The results of this research indicated that the average income of gill net fishermen in Tanjung Laut Indah Village was Rp 15.314.800/month/respondent in the harvest season and Rp 4.634.800/month/respondent in the non harvest season. The average profit of troll line fisherman was Rp. 12.742.033,33/month/respondent in the harvest season and Rp. 9.432.033,33/month/respondent in the non harvest season. The average profit for barrier trap fisherman in Tanjung Laut Indah Village was Rp. 9.619.800/month / respondent in the harvest season and Rp. 3.379.800/ month / respondent in the non harvest season. The profit sharing pattern of catch fisheries business in Tanjung Laut Indah Village that used gill nets, troll line, and barrier trap swhowed the same pattern, that were 50% of profit shared for the owner and 50% for the fishermen crews.